Uncaria gambir Based Green Synthesis of Inorganic Nanoparticles for Photothermal Induced Thrombolytic and Antibacterial Applications - Fithri, Najma Annuria; Mardiyanto; Fadilah, Ade; Pratiwi, Aisyah; Alisyahbana, Sutan Satya; Alhafiz, Muhammad Faris; Maharani, Nabila Puan (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Application of natural compounds in the field of nanoparticle synthesis have been explored due to their robust application and safety. Additionally, these compounds exhibit activities which can be utilised for their medicinal purposes. One of the most useful compounds is catechin, a polyphenolic compound present in high concentration in Uncaria gambir. Herein, we developed inorganic nanoparticles (NPs) based on green synthesis with gambir extract (GE) to produce iron oxide (GE-IONP), gold (GE-AuNP) and silver nanoparticles (GE-AgNP). These nanoparticles were then subjected to observation towards their photothermal activity for the treatment of thrombosis and antibacterial activity. Based on our evaluation, the NPs we obtained were able to exude photothermal effect, indicated by the significant increase of temperature of the solution of around 5-15 ◦C. Evaluation of thrombolytic potential towards thrombus with an in vitro model showed reduction of thrombus mass of around 40-50%, significantly improves the thrombolytic activity compared to GE alone. Antibacterial activity of laser induced GE-AgNP, GE-AuNP and GE-IONP on Escherichia coli and Staphylococcus aureus demonstrated similar strength in inhibiting bacterial growth with broad spectrum antibiotics. Samples containing the NPs that were irradiated with laser were more efficient in preventing bacterial growth when compared to the NPs samples that were not subjected to laser, proving the synergistic mechanism of NPs and laser towards antibacterial effect. Based on the results we obtained, gambir based inorganic particles showed promising results as thrombolytic and antibacterial agent.